How curiosity and uncertainty shape children's information seeking behaviors. Issue 3 (19th September 2016) - Wu, Ko-Chiu; Chen, Hung-Chun
Abstract : Purpose: The purpose of this paper is to explore whether children adopt a survey or a route approach when seeking information in a virtual world (VW), and whether their approach differs depending on whether they are experiencing positive or negative motivation. Different models were used based on disparate spatial recognition and conceptual abilities. Design/methodology/approach: In total, 127 children operated a three-dimensional VW interface then they filled out a questionnaire. Structural equation modeling was employed to analyze weighted relationships among latent variables. Motivation (positive vs negative), information-seeking model (heuristic survey or detailed route) and the spatial markers, and complexity of patterns of the VW were examined. Findings: The authors discovered that a highly motivated child tends to take a central route in the process of information seeking, whereas a child experiencing negative emotions and uncertainty prefers a survey approach using spatial markers to obtain information. In short, the type of motivation influences whether children adopt a heuristic or detailed perspective when searching for information on virtual interfaces. Originality/value: It is believed that users combine perceptual activities (low-level cognition) with conceptual activities (high-level cognition) in order to save energy. Yet this study is the first to investigate the conditions under which children are prone to utilize spatial markers (based on visual working memory) or the sequencing of patterns (based on verbal working memory) to find information in a heuristic or detailed fashion. This study provides a fresh perspective regarding perceptual and conceptual integration for information visualization technology.